Debaryomyces Hansenii: Harnessing its Signification in Kumaun Himalaya’s Traditional Meat Products - Kumar Rai, Arun; Chettri, Arun (Journal of Meat Science, 2026)
The article delves into the prevalence of yeast Debaryomyces hansenii, as  identified by using phenotypic identification following the method of Kreger van Rij and Kurtzman and Fell alongside biochemical assays is notably higher  in traditionally prepared meat products as compared with other yeast genera  from the different pockets of Kumaun Himalayan region. This surveillance is  harmonious with the observation from studies carried out on meat products by  other researchers across the globe. Despite the traditional preparation methods  of meat products adopted by ethnic people of the Himalayas, the occurrence  of this yeast plays a significant role in enhancing the shelf life and highlights  potential avenues for improving food security in resource-constrained  environments. Notably, documenting the indigenous knowledge of traditional  meat processing techniques among ethnic groups residing in remote areas of  the India-Nepal border is arduous. Understanding the microbial ecology of  these items is crucial because it provides insight into the natural processes that  support their preservation. The existence of D. hansenii, a yeast that has been  detected by biochemistry and phenotypic analysis, is rigorously examined in  this paper.
Keywords: Debaryomyces hansenii; Ethnic; indigenous knowledge; food security; Kumaun Himalaya